Listen To Us: A Screenplay Depicting A Community Resistance Against Developmentalism - Gilbert Jeremy Karley; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This creative work, in the form of a short screenplay, examines how a government’s developmental plan can spark collective resistance. Despite the Indonesian government’s efforts to improve social welfare through a series of infrastructure development projects known as the National Strategic Project (PSN), these initiatives can still face opposition from the local rural communities, even if they are as important as healthcare facilities. This resistance stems from factors such as a lack of public participation, environmental degradation, human rights violations, or other intangible losses. This creative work addresses two main problems within the story. Firstly, how the protagonist, Uus, becomes a catalyst for a collective action against a hospital development plan; and secondly, how he navigates the stages of grief after his wife’s death. The work employs theoretical frameworks of Everyday Resistance and the Stages of Grief to analyze these problems. In conclusion, the creative work highlights the emergence of resistance against a benevolent healthcare facility in a rural village, illustrating that grief can be leveraged to mobilize community resistance in the face of development.